Associação entre as condições sanitárias e a incidência de febre Chikungunya no município de Belém, Pará, Brasil - (:unkn) unknown (Universidade Federal de Pernambuco, 2020)
Adequate sanitation is a fundamental requirement for the quality of public health. The objective of this study was to analyze the relationship between access to sanitation services and the incidence of Chikungunya fever in Belém (PA), between 2016 and 2018. Health indicators were developed and determined to the incidence of the disease for the period analyzed. Pearson's correlation identified an association between health conditions and disease incidence. Significant correlations in the incidence of CHIKF occurred between the indicators of quantity and regularity in water supply, solid waste collection and the level of access to sanitation services
Keywords: Febre Chikungunya; Doenças tropicais; Saneamento ambiental